The effect of antioxidant therapy on colonic inflammation in the rat - YEGEN, BERRAK; YÜKSEL, MERAL; ALİCAN, YAŞAR İNCİ (SPRINGER, 1999)
Under normal physiological conditions, chemical and antioxidant defenses protect tissues from the damaging effects of reactive oxygen metabolites (ROM). It has been proposed that ROMs are involved in the development of tissue injury in many inflammatory diseases and also in patients with colitis. In the present study we aimed to investigate the effects of antioxidant therapy on the extent of colonic inflammation and ROM levels in the injured tissues in a trinitrobenzene sulfonic acid-induced colitis model in the rat. Sprague-Dawley rats were pretreated with the antioxidants superoxide dismutase (30,000 U/kg s.c.) or catalase (400,000 U/kg s.c.) prior to induction of colitis and they were decapitated 24 h (acute group) or 6 days (chronic group) after the induction of colitis (each group consists of eight to ten rats). Pretreatment with the antioxidants reduced the macroscopic damage score significantly in both acute and chronic groups compared with untreated colitis groups, whereas they reduced the microscopic damage score and colonic wet weight only in the chronic group. The chemiluminescence assay - a technique to assess the presence of reactive oxygen species in the tissues - values of the groups pretreated with the antioxidants showed a tendency to decrease compared with the untreated colitis group, but they were not statistically significant. Based on these findings, pretreatment with the antioxidants superoxide dismutase or catalase has beneficial effects on the extent of colonic inflammation, particularly in the chronic period, and this may support the importance of antioxidant therapy to reduce the severity of inflammatory bowel disease in humans.
Keywords: colitis; reactive oxygen metabolites; antioxidants; chemiluminescence; rat; DEPENDENT CHEMI-LUMINESCENCE; OXYGEN METABOLITE PRODUCTION; ACID-INDUCED COLITIS; BOWEL-DISEASE; MECHANISM; LUMINOL; CELLS; NEUTROPHILS; MODEL